MENINGKATKAN SINERGI ORANG TUA DAN GURU DALAM PROGRAM DETEKSI PERKEMBANGAN ANAK - Firdaus, Vera (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2021)
Changes that occur in the child's growth and development phase are the result of the maturation process and the learning process. There needs to be a harmonious synergy between parents and teachers to optimize children's development, psychological and physical functions of children. There are children's problems, including: independence, difficulty adapting, temper tantrums, lack of discipline, indulgence, so a program is needed to provide solutions to these problems. This community service provides solutions through the Child Development Detection Program, Counseling and Parenting in 3 kindergarten school locations in Jember. The method used is a qualitative approach. The data were collected through observation, interviews and documentation, then analyzed descriptively. The results of the data indicate the achievement of the program. Community service is able to bridge the perceptions of parents and teachers so that synergies and effective communication are established in order to optimize children's development.